Defining Online Hating and Online Haters - Malecki, W. P.; Kowal, Marta; Dobrowolska, Małgorzata; Sorokowski, Piotr (Frontiers in Psychology, 2021)
According to a view widely held in the media and in public discourse more generally, online hating is a social problem on a global scale. However, thus far there has been little scientific literature on the subject, and, to our best knowledge, there is even no established scholarly definition of online hating and online haters in the first place. The purpose of this paper is to provide a new perspective on online hating by, first, distinguishing online hating from the phenomena it is often confused with, such as trolling, cyberstalking, and online hate speech, and, second, by proposing an operational definition of online hating and online haters based on ethnographic interviews and surveys of the existing scholarly literature.